2017
DOI: 10.6001/actamedica.v24i2.3488
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors characteristic of the patients at the Children’s Ophthalmology Outpatient Department of Kauno klinikos Hospital (Lithuanian University of Health Sciences) from 1 January 2012 to 31 December 2012

Abstract: Background.The purpose of our study was to assess the distribution and patterns of refractive errors in children for the proper planning of paediatric eye care at the centre.Material and methods.The study was conducted in the hospital of the Lithuanian University of Health Sciences in Kaunas, from 1 January 2012 to 31 December 2012. During this period, a total of 11,406 children, aged 0–18 years, were evaluated at the outpatient department of paediatric ophthalmology, Kauno klinikos, the Lithuanian University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…For RE subjects, the light cannot bend correctly because of the uneven shape of the eye, which leads to the lack of light concentration to focus on an image. Therefore, uncorrected RE has long-term implications on patient quality of life, particularly among children [ 34 ]. The current study suggests that subjects with RE (myopia and hyperopia) have a significantly high level of dry eye compared with participants with normal eyes.…”
Section: Discussionmentioning
confidence: 99%
“…For RE subjects, the light cannot bend correctly because of the uneven shape of the eye, which leads to the lack of light concentration to focus on an image. Therefore, uncorrected RE has long-term implications on patient quality of life, particularly among children [ 34 ]. The current study suggests that subjects with RE (myopia and hyperopia) have a significantly high level of dry eye compared with participants with normal eyes.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several epidemiological studies have shown that caesarean delivery and preterm birth increase the risk of childhood myopia. [14][15][16][17] For example, preterm birth may affect ocular development or later emmetropisation, and it may affect the development of the refractive status through a more complicated mechanism. [18][19][20][21][22] In addition, breast feeding in early life may stimulate ocular development, as the docosahexaenoic acid and arachidonic acid in breast milk may affect retinal and neural development, therefore decreasing the risk of myopia.…”
Section: Introductionmentioning
confidence: 99%
“…2 In hypermetropia, the reverse occurs with an image forming posterior to the retinal plane as a result of either in adequate refraction or a short axial lengt. 3 The World Health Organization estimates that 13 million children aged 5-15 years worldwide are visually impaired from uncorrected refractive error. 4 Global action plan 2014-2019 with an aim to reduce prevalence of avoidable visual impairment by 25% by 2019 compared to the baseline prevalence at 2010.…”
Section: Introductionmentioning
confidence: 99%